2009 10th International Conference on Document Analysis and Recognition 2009
DOI: 10.1109/icdar.2009.116
|View full text |Cite
|
Sign up to set email alerts
|

Confidence-Based Discriminative Training for Model Adaptation in Offline Arabic Handwriting Recognition

Abstract: We present a novel confidence-based discriminative training for model adaptation approach for an HMM based Arabic handwriting recognition system to handle different handwriting styles and their variations.Most current approaches are maximum-likelihood trained HMM systems and try to adapt their models to different writing styles using writer adaptive training, unsupervised clustering, or additional writer specific data.Discriminative training based on the Maximum Mutual Information criterion is used to train wr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…It can be observed that both WER and CER are slightly decreasing with every Rprop iteration, and that between 10 and 15 Rprop iterations are optimal for the considered small and unsupervised labeled test datasets. Table 7 shows the final results of our Arabic handwriting recognition system with additional glyph dependent model length estimation (GDL) as described in [6]. Again, the WER of the GDL based system can be decreased by our proposed M-MMI training during both decoding passes down to 14.55%.…”
Section: Second Pass Decoding and Unsupervised Model Adaptationmentioning
confidence: 91%
See 2 more Smart Citations
“…It can be observed that both WER and CER are slightly decreasing with every Rprop iteration, and that between 10 and 15 Rprop iterations are optimal for the considered small and unsupervised labeled test datasets. Table 7 shows the final results of our Arabic handwriting recognition system with additional glyph dependent model length estimation (GDL) as described in [6]. Again, the WER of the GDL based system can be decreased by our proposed M-MMI training during both decoding passes down to 14.55%.…”
Section: Second Pass Decoding and Unsupervised Model Adaptationmentioning
confidence: 91%
“…In addition to the novel confidence-based extension of the margin-based MMI training presented in [6], the confidence concept has been incorporated in the margin-based MPE criterion in this work. In the following, we give a brief summary.…”
Section: Discriminative Training: Incorporation Of the Margin And Conmentioning
confidence: 99%
See 1 more Smart Citation
“…In [4,5] the authors apply a margin-based Maximum Mutual Information (M-MMI) and Minimum Phone Error (M-MPE) training criterion to an HMM-based off-line handwriting recognition system and report up to 33% relative improvement in word error rate (WER) compared to an ML trained baseline system.…”
Section: Introductionmentioning
confidence: 99%
“…Finally each image is re-sized to match the average pixel per character. For isolated words or scripts like Arabic, we could normalize each word to a fixed width keeping their aspect ratio [Dreuw et al 2009]. …”
Section: Width Normalizationmentioning
confidence: 99%